Histological evaluation of MTA as a root-end filling material - Bernabé, Pedro Felício Estrada [UNESP]; Gomes Filho, João Eduardo [UNESP]; Rocha, W. C.; Nery, Mauro Juvenal [UNESP]; Otoboni Filho, João Arlindo [UNESP]; Dezan Junior, Eloi [UNESP] (Blackwell Publishing, 2007)
Aim To assess the histological response associated with grey mineral trioxide aggregate (GMTA) and zinc oxide eugenol (ZOE) as root-end filling materials in teeth where the root canals were not filled and the coronal access cavities were not restored.Methodology Periapical lesions were developed in 24 premolar teeth in three dogs. The root canals were prepared and half of them were dried, filled and the coronal access restored (closed). The remaining teeth were not root filled and no coronal restoration was placed (open). Apical root-end resections were performed 3 mm from the apex, and root-end cavities were prepared with ultrasonic tips. These were randomly filled with either ZOE or GMTA in the same number of specimens using MAPSYSTEM device. After 180 days the animals were killed and blocks of tissues removed and processed for histological examination. Periradicular tissue reaction was evaluated, including severity of inflammation and cementum formation. Statistical analysis was performed using ANOVA analysis and Tukey's test.Results A significant difference was found between the levels of inflammation in the periradicular tissues of the GMTA/closed group, compared with the ZOE/open and ZOE/closed groups (P < 0.05) but not between GMTA/closed and GMTA/open groups. Cementum formation was not found over any ZOE specimens but over MTA in all specimens. No microorganisms were found in the interface between the material and the dentinal walls.Conclusions GMTA was associated with less periapical inflammation and tissue response when used as a root-end filling material, even when no root filling or coronal restoration was present.
Keywords: apicectomy; MTA; sealability; tissue response